High Performance Sensors Using Graphene Based Organic-Inorganic Hybrids - S. Kwon, Oh; Hur, Jaehyun; Koh, Dongsoo; Bae, Joonwon (Current Organic Chemistry, 2014)
Graphene has become one of the most exciting materials in the fields of science and technology, owing to their excellent physical, chemical, electrical, and mechanical properties. In general, the introduction of secondary components to graphene substrates can be a lucrative pathway to obtain improved performances. Attention has been paid to the sensing capabilities and compatibilities of graphene based materials. Therefore, to date, high-performance graphene nanostructures have been successfully fabricated and have shown excellent sensing performances. In addition, graphene or graphene hybrid scan be integrated into field-effect transistor (FET) and chemoresistive systems to obtain signal amplification and enhanced sensing properties, leading to high-performance novel graphene sensors. Consequently, in this mini-review article, we summarize recent research activities on novel graphene-based chemical and biological sensors. This article can provide information on cutting edge sensor technologies encompassing recent research efforts.
Keywords: polymer